2019
DOI: 10.1101/641142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accuracy, Robustness and Scalability of Dimensionality Reduction Methods for Single Cell RNAseq Analysis

Abstract: Background: Dimensionality reduction (DR) is an indispensable analytic component for many areas of single cell RNA sequencing (scRNAseq) data analysis. Proper DR can allow for effective noise removal and facilitate many downstream analyses that include cell clustering and lineage reconstruction. Unfortunately, despite the critical importance of DR in scRNAseq analysis and the vast number of DR methods developed for scRNAseq studies, however, few comprehensive comparison studies have been performed to evaluate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 84 publications
(97 reference statements)
2
8
0
Order By: Relevance
“…type identification as a downstream task of DR. Both measures are frequently used to assess the performance of cell embedding techniques [18,11,20,23,10]. Another standard measure to assess the ability of a clustering algorithm to recover known classes is the adjusted rand index (ARI) [11,20,23,10]; however, we found that AMI and ARI are extremely correlated (Additional file 1: Fig.…”
Section: Plates Basedmentioning
confidence: 93%
See 1 more Smart Citation
“…type identification as a downstream task of DR. Both measures are frequently used to assess the performance of cell embedding techniques [18,11,20,23,10]. Another standard measure to assess the ability of a clustering algorithm to recover known classes is the adjusted rand index (ARI) [11,20,23,10]; however, we found that AMI and ARI are extremely correlated (Additional file 1: Fig.…”
Section: Plates Basedmentioning
confidence: 93%
“…Many computational methods have therefore been developed in recent years to take into account the specificities of scRNA-seq data and address the issues of data normalization, cell type identification, differential gene expression analysis, cell hierarchy reconstruction, or gene regulatory network inference (see [8,9] for recent reviews). In order to help practitioners choose an analysis pipeline among the many available, several studies have benchmarked algorithms and softwares for applications such as dimensionality reduction [10], clustering [11,12], differential expression [13], or trajectory inference [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some methods, especially those using deep learning, depend strongly on choice of hyperparameters [94]. There, more detailed comparisons that explore parameter spaces would be helpful, extending work like that from Sun et al [95] comparing dimensionality reduction methods. Such detailed benchmarking would also help to establish when normalization methods derived from explicit count models (e.g., [96,97]) may be preferable to imputation.…”
Section: Open Problemsmentioning
confidence: 99%
“…Dimensionality reduction is very beneficial and vital when evaluating high dimensional data [57], it is an essential analytic factor for RNA-seq data analysis. Appropriate dimensionality reduction algorithms can facilitate effective evaluations and classification performance of different approaches in relation to their capability to improve features of the innovative expression in terms of their performance metrics such as accuracy, sensitivity, specificity, recall, robustness, computational scalability, computational cost, among others [58].…”
Section: A Review Of Dimensionality Reduction Technologiesmentioning
confidence: 99%